PENERAPAN APLIKASI DATABASE PADA KEGIATAN MANAJEMEN USAHA DI KAFE SENECA - Muhammad Fadlan; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of this research is to evaluate the use of a database system in data processing and meet system requirements for hardware and software as well as user needs for cafe management. The research method used is qualitative, with data collection through observation, interviews and documentation. The research was conducted in a cafe in the city of Medan involving baristas and cafe waiters as informants. The research results show that only a few cafes use database applications for data management; system requirements (hardware and software) have been adjusted to technological advances; and user needs (brainware) have been met with continuous training to improve the capabilities of the workforce in the cafe.